The IASP classification of chronic pain for ICD-11 - applicability in primary care - Smith, Blair H.; Fors, Egil; Korwisi, Beatrice; Barke, Antonia; Cameron, Paul; Colvin, Lesley; Richardson, Cara; Rief, Winfried; Treede, Rolf-Detlef (Pain, 2019)
AbstractThe International Classification of Diseases, 11th Revision (ICD-11), proposes, for the first time, a coding system for chronic pain. This system contains 1 code for “chronic primary pain,” where chronic pain is the disease, and 6 codes for chronic secondary pain syndromes, where pain develo